The Effect of Social Responsiveness on Infants' Object‐Directed Imitation. (23rd August 2016) - Miller, Jennifer L.; Gros‐Louis, Julie
Abstract : Previous research has demonstrated that social interactions underlie the development of object‐directed imitation. For example, infants differentially learn object action sequences from a live social partner compared to a social partner over a video monitor; however, what is not well understood is what aspects of social interactions influence social learning. Previous studies have found variable influences of different types of caregiver responsiveness on attention, language, and cognitive development. Therefore, the purpose of this study was to examine how the responsive style of a social partner influenced the learning of object‐directed action sequences. Infants interacted with either a sensitive or redirective experimenter before the learning trial. Results revealed infants changed their patterns of engagement; infants interacting with a sensitive experimenter had longer periods of attentional engagement than infants interacting with a redirective experimenter. Furthermore, during the learning trial, the amount of sensitivity during interaction with the social partner predicted learning scores. These findings suggest that infants' attention is influenced by social partners' interactive style during ongoing interaction, which subsequently affects how infants learn from these social partners.